(untitled) (Communications in Computational Physics, 2010)
We investigate the dynamics of a system coupled to an environment by averaged semiquantum method. The theory origins from the time-dependent variational principle (TDVP) formulation and contains nondiagonal matrix elements, thus it can be applied to study dissipation, measurement and decoherence problems in the model. In the calculation, the influence of the environment governed by differential dynamical equation is incorporated using a mean field. We have performed averaged semiquantum method for a spin-boson model, which reproduces the results from stochastic Schrodinger equation method and Hierarchical approach quite accurately. Moreover, we validate our results with noninteracting-blip approximation (NIBA) and generalized Smoluchowski equation (GSE). The problem dynamics in nonequilibrium environments has also been studied by our method. When applied to the harmonic oscillator model coupled to a heat bath with different coupling strengths and dimensionalities of the bath, we find that the loss of coherence predicted by semiquantum method is identical to the result of master equation with different initial state (Gaussian wave packet and superposed wave packets).